2012
DOI: 10.5586/aa.2005.009
|View full text |Cite
|
Sign up to set email alerts
|

Research on the development of Mycosphaerella graminicola (Fuckel) Schroeter teleomorph on wheat leaves from Poland and Czech Republic

Abstract: S u m m a r yThe aim of the work was to study the development of pseudothecia of M. graminicola. The experiment was carried out in 2002/2003. Wheat leaves collected at Koñczewice (near Toruñ), S³upia Wielka (near Poznañ) and Kromìøí• (Czech Republic) were kept on an experimental field in Warsaw. The pseudothecia were observed under the light and transmission electron microscopy.The first pseudothecia were observed on the dead leaves at the end of July. The largest number of fruiting bodies were noted in Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A positive correlation was determined for the first day of maximum rainfall (r = 0.328) in May, while in June, both the daily maximum sum of rainfall and the monthly sum of rainfall were significantly correlated to the occurrence of P. nodorum (r = 0.290 and r = 0.287, respectively). Numerous studies confirmed the relationship between the frequency of rainfalls and successful infection by P. nodorum, leading to the development of disease symptoms of glume and leaf blotch [3,22,23]. According to Głazek et al [17], rainfalls in June were of key importance in Poland.…”
Section: Correlation Between Meteorological Factors and Occurrence Of P Nodorummentioning
confidence: 95%
See 1 more Smart Citation
“…A positive correlation was determined for the first day of maximum rainfall (r = 0.328) in May, while in June, both the daily maximum sum of rainfall and the monthly sum of rainfall were significantly correlated to the occurrence of P. nodorum (r = 0.290 and r = 0.287, respectively). Numerous studies confirmed the relationship between the frequency of rainfalls and successful infection by P. nodorum, leading to the development of disease symptoms of glume and leaf blotch [3,22,23]. According to Głazek et al [17], rainfalls in June were of key importance in Poland.…”
Section: Correlation Between Meteorological Factors and Occurrence Of P Nodorummentioning
confidence: 95%
“…For sites above the disease threshold, a quantitative model predicted the severity of Z. tritici using rainfall during stem elongation. According to studies by Mirzwa-Mróz et al [23], the pseudothecia of M. graminicola emerged from June to January under favourable climatic conditions. Henze et al [38] in Germany, in 1995-2003, determined the impact of humidity, rainfall and temperature on outbreaks of Z. tritici.…”
Section: Correlation Between Meteorological Factors and Occurrence Of Z Triticimentioning
confidence: 99%